ASUPAN ASAM FOLAT, VITAMIN B12 DAN VITAMIN C PADA IBU HAMIL DI INDONESIA BERDASARKAN STUDI DIET TOTAL - Astriningrum, Eka Puspita; Hardinsyah, Hardinsyah; Nurdin, Naufal Muharam (The Food and Nutrition Society of Indonesia in collaboration with the Department of Community Nutrition, IPB University, 2017)
This study aimed to analyze intake of folic acid, B12 and C of pregnant women (PW) in Indonesia. This study used secondary data from a cross-sectional study, so called Total Diet Study conducted in year 2014. The food consumption data were collected using the 24-hour dietary recall method. Total subjects of this study were 606 PW aged 14-49 old. Data of dietary intake of folic acid, vitamin B12, and vitamin C were analyzed using Indonesian food composition tables (FCT), nutrisurvey software, nutrition fact and FCT from United States Department of Agriculture (USDA). The results showed that mean intake of folic acid, vitamin B12 and vitamin C were 167.2±145.5 µg/d, 3.5±5.3 µg/d, 61.3±75.8 mg/d, respectively. The prevalence of severely deficiency of folic acid, vitamin B12 and vitamin C were 88.3%, 34.5% and 46.9% respectively. Logistic regression analysis showed that the younger PW from middle and low economic status had higher risk for folic acid deficiency. PW with education level less than and equal to senior high school with middle and low economic status had higher risk for vitamin B12 deficiency. PW with education level less than and equal to senior high school had higher risk for vitamin C deficiency. Consumption of folic acid, vitamin B12 and vitamin C of PW was low, so the consumption of vitamin sources was very important to prevent problems during pregnancy, such as anemia, premature, and also maternal and child mortality.